2013
DOI: 10.1089/bio.2013.0025
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for Biochemical and Pathologic Quality Assurance in a Large Multi-Institutional Biorepository; The Experience of the PROCURE Quebec Prostate Cancer Biobank

Abstract: Well-characterized, high-quality fresh-frozen prostate tissue is required for prostate cancer research. As part of the PROCURE Prostate Cancer Biobank launched in 2007, four University Hospitals in Quebec joined to bank fresh frozen prostate tissues from radical prostatectomies (RP). As the biobank progressed towards allocation, the nature and quality of the tissues were determined. RP tissues were collected by standardized alternate mirror-image or biopsy-based targeted methods, and frozen for banking. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 20 publications
(25 reference statements)
0
13
0
Order By: Relevance
“…Of the 15 studies assessed, 13 investigated quality of tissue biospecimens from various cancers, including pancreatic, colorectal, breast, bladder, ovarian, and head and neck 17–29. Overall, 93% of studies reported at least two diagnostic and two predictive measures of quality,12 17–24 26–30 with the majority of studies (53%) reporting at least six of the nine diagnostic and/or predictive quality measures 12 18 20–22 27–29. Moreover, of those, 25% of studies reported at least seven of the nine measures of interest 21 28…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 15 studies assessed, 13 investigated quality of tissue biospecimens from various cancers, including pancreatic, colorectal, breast, bladder, ovarian, and head and neck 17–29. Overall, 93% of studies reported at least two diagnostic and two predictive measures of quality,12 17–24 26–30 with the majority of studies (53%) reporting at least six of the nine diagnostic and/or predictive quality measures 12 18 20–22 27–29. Moreover, of those, 25% of studies reported at least seven of the nine measures of interest 21 28…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the majority of these studies (73%) reported storage of tissue biospecimens at −80°C,12 17–19 22–24 26–29 30 despite best practice guidelines suggesting tissue biospecimens should be stored long term at −196°C 14. Transit time from surgical resection to time of cryopreservation was reported by 9 of 15 studies, with times ranging from instantaneous fixation in theatre to 72 h 12 18 21–24 27–29. However, transit temperature was recorded infrequently, with only 27% of studies recording this outcome measure19–21 28 and the majority (3/4) transporting specimens at 4°C 20 21 28…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Half the tissue was de-identified and handed off to lab personnel for tissue culture. The second half, known as the ''mirror image,'' was read by the pathologist and then stored in the tissue bank as a FFPE block with a corresponding hematoxylin and eosin-stained slide cut from that block [23,24].…”
Section: Tissue Procurementmentioning
confidence: 99%